Enhanced Thermal Performance of Parabolic Through Collectors with TiO₂ Nanofluids in An Arid Climate - Belhadi, Mohammed Abdelkrim; Kadja, Mahfoud; Mechighel, Farid; Khechekhouche, Abderrahmane; Hamaiti, Youcef (Indonesian Journal of Science and Technology, 2025)
Solar energy is a crucial renewable resource, yet its efficient utilization remains a challenge because conventional heat transfer fluids have limited thermal conductivity. Parabolic Trough Collectors (PTCs) offer a viable solution for solar thermal energy conversion, but optimizing performance is essential for improving efficiency. This study investigates the performance of a PTC using a 0.3% TiO₂-water nanofluid compared to distilled water (DW) under real environmental conditions in Algeria’s arid climate. Two identical PTCs were tested outdoors at flow rates of 0.2, 0.3, and 0.4 L/min to evaluate heat transfer efficiency. The results demonstrated that the nanofluid consistently outperformed DW because of its superior thermal conductivity and heat retention. At 0.4 L/min, the nanofluid achieved 40% thermal efficiency, 9% higher than DW. However, as the flow rate decreased, the efficiency gap narrowed. These findings confirm the potential of nanofluids to enhance solar energy utilization, supporting sustainable energy solutions in high-irradiance regions.